“I Needed to Rediscover who I Really Was”: An Inquiry into the Impacts of one Graduate Teacher Education Program for Early Elementary Teachers (Alberta Journal of Educational Research, 2018)
This paper reports on the impacts on teachers of a new Masters in Education program developed for early elementary teachers at one small Canadian university. Central to the program are concepts of the child as competent and capable, and a view of professional learning as democratic, critically reflective and a way to enhance teacher agency. Our findings are based on interviews and focus group conversations with several members of one of the cohorts who completed the program. In our thematic analysis we determined that teachers reported changes in their practices including slowing down and listening to children as well as increased flexibility and ability to relinquish control. Additionally, teachers spoke of increased confidence in themselves and the children in their classrooms as a result of participating in this program.Keywords: early elementary grades, graduate teacher education, early elementary pedagogy, democratic professional learning, teachers’ agencyCet article fait état des impacts sur les enseignants d’un nouveau programme de maitrise en éducation développé par une petite université canadienne pour les enseignants du primaire. Le programme est centré sur le concept selon lequel l’enfant est compétent et capable, et sur une perspective de l’apprentissage professionnel comme étant un processus de réflexion critique qui est démocratique et susceptible d’augmenter chez les enseignants le sentiment de pouvoir agir. Nos résultats découlent d’entrevues et de conversations avec des groupes de discussion impliquant plusieurs membres d’une cohorte ayant complété le programme. Notre analyse thématique révèle que les enseignants ont signalé des changements dans leurs pratiques; entre autres, ils ont indiqué qu’ils ralentissaient et écoutaient les élèves, étaient plus souples et se sentaient en mesure de céder le contrôle. De plus, les enseignants ont reconnu que leur participation au programme avait entrainé une augmentation de leur confiance en soi et en les élèves.Mots clés : premières années du primaire, études supérieures en enseignement, pédagogie des premières années du primaire, sentiment chez les enseignants de pouvoir agir.